Design and Realization of Multiplexing System for Fixed/Mobile Next-Generation Broadcasting Service in Network Free Environment - Y.J. Woo; K.W. Park; W.G. Jeon; J.H. Paik; G.M. Kang; K.W. Kwon (Institute of Advanced Engineering and Science, 2015)
The Current broadcasting enviroment is constally evolving in order to meet the various needs of the viewer such as ColorTV, 3D, HD, UHD TV serivce. And they want to broadcasting the same quality in the fixed and mobile enviroment for high definition braodcasting serive. In this paper, we presnet a design and implementation of muilplexing system for fixed/mobile next generation broadcasting service in network free enivorment. Network free means receive both the broadcasting channel and communication chennel for various TV service. We introduce method to provide next generation convergence broadcating servies based on european standard which can transmit UHD content in network free envieroment. As a result to this paper, we analyze the characteristics of the recieved signal from the commerical receiver device.